Internalisation of Moderate Religious Values in Religious Diversity Among Student at Public Junior High School in Jayapura - A, Patmawati; Umkabu, Talabudin; Zulihi, Zulihi (International Tatho Academics, 2026)
The purpose of this study is to describe the paradigm of disseminating moderate character values to students by Islamic Religious Education teachers at Sentani 1 Public Junior High School. This qualitative study is a case study. Data were obtained through interviews, observations, and documentation. This study is supported by the theory of interfaith collaboration, the theory of value internalisation, and a preventive approach in religious education. The results of the study indicate that there is an integration paradigm in the dissemination of moderate religious values by Islamic Education teachers at the school, namely through interrelated strategies in strengthening moderate values in the curriculum, using a local culture-based approach, and cultivating tolerant attitudes in daily interactions. These strategies create an inclusive and harmonious learning environment and foster tolerant attitudes among students. This study contributes to the importance of holistic strategies in the internalization of moderate religious diversity among students, emphasizing cognitive, affective, and psychomotor aspects.